Surgical variables analysis of 116 cases of ovarian cystic diseases in Al- Elwiya maternity teaching hospital at 2013 - Hasan, Samer F.; Hasaani, Harith S.; AbdAL-Hameed, Jamal R. (AL-Kindy College Medical Journal, 2014)
Background: The treatment of an ovarian cyst relies on its nature, the discrimination of benign and malignant cysts is, therefore of crucial importance, and in spite of the continuous improvement of diagnostic means, it remains sometimes impossible to differentiate functional from organic (malignant or not) ovarian cysts. The therapeutic decision will search for the main midway between cancer’s negligence and the fear of performing an unnecessary surgical operation for an ovarian cyst.Objective: To review of 116 cases of ovarian cystic diseases aiming in identify proper management and reducing unnecessary surgical intervention.Methods: A retrospective study was conducted at Al-Elwiya maternity teaching hospital/ Baghdad/ Iraq. One hundred sixteen women underwent surgery for ovarian cystic diseases between January 2010 and December 2011. Age, menopausal status, referral history, clinical features, diagnostic methods, treatments and histopathological results were recorded and the collected data was arranged in tables for analysis.Results: From One hundred sixteen women, One hundred five (90.5%) were premenopausal and eleven (9.5%) were postmenopausal. Thirty two women (27.6%) underwent laparoscopic evaluation for Ovarian cystic diseases, while eighty four (72.4%) were candidates for laparotomy. Benign pathological conditions were found in thirty six (31%) pre-menopausal women and three (2.6%) post-menopause. The functional cysts presented in sixty of the cases (51.7%), Fifty five (47.4%) were premenopausal and five (4.3%) postmenopausal.Conclusion: There is difficulty in accurate discrimination between types of ovarian cysts In Iraq and we recommend to use risk of malignancy index (RMI) as a simple diagnostic tool that provide to discriminate between malignant and benign ovarian cysts.Keywords: Ovarian cystic diseases, risk of malignancy index (RMI)